The Policy of Virginity Testing in the Indonesian Military from the Perspectives of Public Values and Control toward Bureaucratic Discretion - Aulia Shifa Hamida (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
As an agent who implements government policies (principals), it remains a heated debate about whether bureaucracy should be value-neutral or must adhere to public values and administrative ethics. In response to this debate, the author uses the case study of virginity testing in the Indonesian National Armed Forces as one example of maladministration which proves that the bureaucracy, as institution, structure, or procedure, shall require administrative ethics, as a means to preserving public values. The research methodology used is that of literature review on public values, administrative ethics, and control mechanisms over bureaucratic discretion to prove that the virginity testing has unequivocally violated the TNI code of ethics, Law No. 34 of 2004 concerning TNI, international law, public opinion, medical science, and the code of ethics of the military profession. The author uses both deductive and inductive approaches to form policy recommendations for TNI reform in terms of its of policies, governance, and institutions in accordance with public values, administrative ethics, and control mechanisms over bureaucratic discretion; such as strengthening the internal performance audit of the TNI, establishing an independent external performance audit agency, establishing a Truth and Reconciliation Commission, and revising the Law on Government Administration to limit bureaucratic discretion.